In the light of the future. The age of image and reality (Confluenţe Bibliologice, 2012)
20 years ago in the library community was integrated a new University Library – Information and Library Science Department of Free International University of Moldova. During these years has been formed a professional team, were created various info-documentary collections, new services, digital library, institutional repository, were realized institutional projects, national and international.
Keywords: scientific conferences